Perrotta Integrative Clinical Interview (PICI-1): A new revision proposal for PICI-1TA. Two single cases - Perrotta, Giulio (Global Journal of Medical and Clinical Case Reports, 2021)
Purpose: This research aims to reinforce the credibility of the PICI-1 psychodiagnostic instrument by making some corrections that are immediately evident in several clinical cases. Among all, the proposed case represents the clearest and most effective example. Methods: Clinical interview and administration of the MMPI-II, PICI-1 and PSM-1. Results: On the basis of specific clinical observations, evident in the proposed cases, the following corrections to the basic PICI-1 model have been suggested: 1) at the diagnostic level: the diagnosis must take into account the first two highest levels of dysfunctional traits, considering the next three lower levels as elements of psychotherapeutic interest. In the hypothesis of dysfunctional hyperactivation, the diagnosis should be re-evaluated at the end of the psychotherapeutic pathway; 2) on the unitary diagnosis: the diagnosis takes into account, in its final formulation, the primary disorder (P, main diagnosis), co-primary disorders (M, mixed diagnosis), comorbidities (C), secondary disorders (S), and tertiary traits (T); 3) on the symptomatic persistence of symptoms and on the plasticity of the personality: mindfulness can aid change, as long as it is real, concrete, and current, and the complained of dysfunctional traits have not been present for a long time (more than 1 year, anyway); 4) on absorptions: anxiety disorder absorbs somatic disorder, phobic disorder, and manic disorder, the latter becoming specific traits of anxiety (main) disorder; psychotic disorders absorb all other neurotic disorders. Conclusions: The results obtained from the two proposed clinical cases suggest the following modifications to the model. These corrections actually facilitate the psychological course and the diagnostic interpretation of the patients, who were able to alleviate their suffering to an acceptable level of tension, without pharmacological support.